Advancing community viability analysis: assessing community resistance and persistence of Mojave Desert birds to climate change - Eichenwald, Adam. (Tufts University. Tisch Library., 2024)
Thesis (Ph.D.)--Tufts University, 2024.; Submitted to the Dept. of Biology.; Advisor: Michael Reed.; Committee: Elizabeth Crone, Ben Wolfe, Colin Orians, Zarin Machanda, and Morgan Tingley.; Keywords: Ecology, Environmental science, and Conservation biology.